Inovasi Manajemen Pembelajaran PAI Melalui Media Interaktif Digital pada Generasi Z - Nur Mila Maddu; Try Susanti; Anita Anita; Muhammad Almansyawwi; Rizqi Firmansyah (MAN 4 Kota Pekanbaru, 2025)
Digital transformation in the era of the Industrial Revolution 4.0 demands innovation in Islamic Religious Education (IRE) learning management, particularly to accommodate the characteristics of Generation Z, who are highly familiar with technology and prefer interactive, visual, and experiential learning. This study focuses specifically on analyzing the management of IRE learning through the integration of digital interactive media, covering planning, organization, implementation, evaluation, and the development of students’ religious character. Employing a qualitative library research approach, data were collected from books, national journal articles, proceedings, and relevant educational policy documents published between 2016 and 2024. Data analysis followed a systematic descriptive-analytical procedure. The findings indicate that innovations such as Learning Management Systems (LMS), interactive videos, gamification, technology-based worship simulations, religious e-portfolios, and digital projects significantly enhance student engagement, deepen religious understanding, and support the internalization of Islamic values among Generation Z. The study confirms the strategic role of digital interactive media in creating adaptive, effective, and relevant IRE learning, emphasizing the need for adequate infrastructure, teacher digital literacy, and institutional support.